(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Based on the study of the current-voltage dependences during the joint electroreduction of rhenium and molybdenum ions from sulfate electrolytes on the nickel electrode, the conditions for the deposition of alloy nanocoatings in the Re-Mo system were established. The influence of various factors on the composition and quality of coatingswas studied: the content of components in the electrolyte, current density, temperature, acidity of solutions, etc., It has been established that, with an increase in the content of rhenium in the electrolyte and current density, the content of rhenium in the alloy increases. Based on the experimental data, the following electrolyte composition (mol/l) is recommended to obtain semiconductor rhenium-molybdenum alloys containing 35-50% Re: electrolyte (mol/l): 1.5 10-3 Na2MoO4 + 3.5 10-3 KReO4 + 2.0 H2SO4 ; pH=0.4; Ev=0.005 Vs-1 t=75C, electrode Pt.